Implementasi Kegiatan Ekstrakulikuler terhadap Pendidikan Karakter Siswa di SMA Negeri 1 Panyabungan - Siti Masitoh Lubis; Novebri Novebri (Lembaga Pengembangan Kinerja Dosen, 2025)
Character education is one of the important aspects in the world of modern education, especially in Indonesia which makes national character building a major vision of national education. This article aims to explore the implementation of extracurricular activities in supporting student character education at SMA Negeri 1 Panyabungan. Through structured activities such as sports, arts, scouts, and social activities, students are introduced to values ​​such as responsibility, cooperation, tolerance, and leadership. The results of this article show that extracurricular activities play a significant role in developing student character, creating individuals with integrity, independence, and are ready to face various challenges in life.